Nivolumab as a promising treatment option for metastatic salivary duct carcinoma - Bugia, Luis; Jungbauer, Frederic; Zaubitzer, Lena; Hörner, Christian; Merx, Kirsten; Yasser, Abo-Madyan; Germann, Thomas; Lammert, Anne; Scherl, Claudia; Rotter, Nicole; Affolter, Annette (Journal of immunotherapy, 2024)
Salivary duct carcinomas (SDC) of the parotid gland are rarely occurring highly malignant tumors. A 65-year-old man presented with a preauricular mass. After surgical treatment and histologic examination, the findings were interpreted as a squamous cell carcinoma (SCC) metastasis of the parotid gland deriving from a cancer of unknown primary DD primary SCC of the parotid gland. Adjuvant platinum-based radiochemotherapy was administered in domo. However, re-staging revealed multiple size-progressive pulmonary round lesions. After resection and histological examination of a pulmonary mass and in synopsis with the primary tumor, the initial diagnosis of SCC was revised to SDC of the parotid gland. With positive HER-2 status, off-label trastuzumab/docetaxel was initiated in an individual healing attempt, during which the pulmonary metastases showed clear progression. Consequently, the patient received immunotherapy with nivolumab according to his negative PD-L1 status. After 57 cycles of nivolumab, the patient presents with partial remission and in good condition. We report, for the first time, a robust response of metastatic SDC to checkpoint inhibition with nivolumab without additional radiotherapy.